Britain's position on non-tariff protection - Hindley, Brian (London : Trade Policy Research Centre, 1972)
This paper was prepared as part of an international programme of studies on the negotiating positions of governments in dealing with non-tariff barriers and deals with the British situation.
Includes bibliographical footnotes.
osc 10/07/2018
Loans
Keywords: International Trade; Non-Tariff Trade barriers; Britain